The Role and Functions of Synonyms in Literary Texts - Adjeminova , Elvina (The Lingua Spectrum, 2025)
This article explores the functional potential of synonyms in literary texts, their role in creating expressiveness, stylistic diversity, and semantic nuances. Various types of synonyms are examined, including semantic, stylistic, and contextual ones, as well as their impact on imagery and emotional expressiveness in a work of literature. Special attention is given to the role of synonymic series in conveying the author’s intent, enhancing the writer’s individual style, and achieving artistic effect. The use of synonymy in expressive techniques such as repetition, gradation, and contrast is analyzed. The study is based on materials from Russian and foreign literature, allowing for the identification of universal patterns and specific authorial techniques. A conclusion is drawn regarding the significance of synonyms as one of the key tools of linguistic variability, influencing the structure and composition of a literary text.